Perbandingan Latihan Hatha Yoga dan Senam Lansia terhadap Kebugaran Kardiorespirasi Lansia - Pramudhita, Ardina Nur; Ambarwati, Endang; Putri, Rahmi Isma Asmara (Majalah Kedokteran Indonesia, 2025)
Introduction: Cardiorespiratory fitness declines with age. Regular exercise helps enhance an elderly person’s physical capacity, fitness, and overall quality of life. Senam lansia is physical activity that is frequently performed by the elderly population. Though hatha yoga has slower movements than exercise for the elderly, it still incorporates various exercise component. This study was aimed to assess the difference between hatha yoga exercise and senam lansia on cardiorespiratory fitness of the elderly.Methods: This study was a randomized controlled pre- and post-test. The hatha yoga group and the control group were randomly selected with a total of 26 participants. For six weeks, three times a week, participants in the intervention group and control group performed hatha yoga and senam lansia, respectively. The six-minute walk test is used to measure maximum oxygen consumption (VO2 max), a measure of cardiorespiratory fitness.Result: The mean VO2max value was 15.03 ± 2.63 ml/kg/minute in the hatha yoga group and 13.82 ± 2.05 ml/kg/minute in the senam lansia group with significant differences between groups. The increase in VO2 max values before and after the intervention was 1.83 ± 1.15 ml/kg/minute in the hatha yoga group and 1.35 ± 1.04 ml/kg/minute in the senam lansia group with no significant difference between the two groups.Conclusion: Hatha yoga exercises and senam lansia have the similar effect on increasing cardiorespiratory fitness as measured by the 6-minute walk test.